Epidemiology of Community-Acquired Sepsis in Adult Patients: A Six Year Observational Study - Grozdanovski, Krsto; Milenkovikj, Zvonko; Demiri, Ilir; Spasovska, Katerina; Cvetanovska, Marija; Saveski, Velimir; Grozdanova, Biljana (Macedonian Academy of Sciences and Arts/Sciendo, 2018)
Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to an infection and it is a major cause of morbidity and mortality worldwide. The aim of this study is to describe epidemiology of community-acquired sepsis in the Intensive care unit (ICU) of the Macedonian tertiary care University Clinic for Infectious Diseases. A prospective observational study was conducted over a 6-year period from January, 2011 to December, 2016. All consecutive adults with community-acquired sepsis or septic shock were included in the study. Variables measured were incidence of sepsis, age, gender, comorbidities, season, source of infection, complications, interventions, severity indexes, length of stay, laboratory findings, blood cultures, 28-day and in hospital mortality. Of 1348 admissions, 277 (20.5%) had sepsis and septic shock. The most common chronic condition was heart failure (26.4%), and the most frequent site of infection was the respiratory tract (57.4%). Median Simplified Acute Physiology Score (SAPS II) was 50.0, and median Sequential Organ Failure Assessment (SOFA) score was 8.0. Blood cultures were positive in 22% of the cases. Gram-positive bacteria were isolated in 13% and Gram-negatives in 9.7% of patients with sepsis. The overall 28-day and in hospital mortality was 50.5% and 56.3% respectively. The presence of chronic heart failure, occurrence of ARDS, septic shock and the winter period may influence an unfavorable outcome. Mortality compared to previous years is unchanged but patients that we have been treating these last 6 years have had more severe illnesses. Better adherence to the Surviving Sepsis guidelines will reduce mortality in this group of severely ill patients.
Keywords: epidemiology; mortality; sepsis; septic shock; severe sepsis